2013
DOI: 10.1007/s00198-013-2464-9
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 21 (FGF21) and bone: is there a relationship in humans?

Abstract: This study reveals for the first time a strong positive association between plasma FGF21 levels and BMD in healthy women, suggesting the association between bone loss and high FGF21 states in animals may not be directly translated to humans in physiologic states. We hypothesize that FGF21 may increase bone mass particularly in women through paracrine mechanisms in the bone-adipose interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 19 publications
1
38
1
Order By: Relevance
“…25 A link between energy expenditure, metabolism, and bone mass certainly exists with adiponectin and endocrine FGFs potentially playing direct roles. 18, 41 Both increased FGF21 and adiponectin lead to bone loss in mice and adiponectin and thiazolidinedione drugs (which elevate adiponectin) are both linked to reduced bone mass and osteoporosis. 18, 21, 41 We found reduced FGF23 in APN-Tg mice and elevated levels in APN KO mice on normal chow, a result similar to one clinical study that found an inverse relationship between these hormones.…”
Section: Discussionmentioning
confidence: 99%
“…25 A link between energy expenditure, metabolism, and bone mass certainly exists with adiponectin and endocrine FGFs potentially playing direct roles. 18, 41 Both increased FGF21 and adiponectin lead to bone loss in mice and adiponectin and thiazolidinedione drugs (which elevate adiponectin) are both linked to reduced bone mass and osteoporosis. 18, 21, 41 We found reduced FGF23 in APN-Tg mice and elevated levels in APN KO mice on normal chow, a result similar to one clinical study that found an inverse relationship between these hormones.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, the level of circulating FGF21 is positively correlated with carotid intima-media thickness only in women but not in men [36]. Similarly, Lee et al observed that circulating FGF21 level is not correlated with bone mineral density (BMD) in man but it is positively correlated with BMD in healthy women even after adjustment for age and body composition [65]. It will be intriguing to know if the interaction between gender and FGF21 plays a role in its association with diabetes complications and the long-term outcome of FGF21 mimetic therapy.…”
mentioning
confidence: 84%
“…With regards to chronic exercise, Bostrom et al ) also found no effect of long-term training on irisin level. Browning of WAT has not been observed after irisin/FNDC5 treatment in vitro (40,135) in humans. A study investigating the effect of FNDC5 treatment on human adipose cells found that UCP1 mRNA expression increased predominantly in classical brown adipocytes rather than white adipocytes (40).…”
Section: Assessment Of Bat and Browningmentioning
confidence: 96%
“…SNS activation is reflected by an increase in plasma and urinary noradrenaline levels in cold-exposed subjects (35,38,39,40,41). Denervation of sympathetic nerves abrogated the cold-induced changes in BAT activity in animals (42), providing strong evidence that SNS plays a pivotal role in mediating the stimulatory effect of cold on BAT.…”
Section: Assessment Of Bat and Browningmentioning
confidence: 99%